Analisis Eksistensi Humas CRN TV sebagai Media Jurnalisme di Fakultas Ilmu Sosial UIN Sumatera Utara Medan - Kurniawan, Ade; Saragih, Yose Rizal (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2024)
The importance of the journalistic function of CRN TV's Public Relations in providing accurate information and fostering two-way dialogue between institutions and the public, particularly within the educational environment, is the focus of this study. The aim of this research is to identify and evaluate PR strategies in leveraging digital technology to enhance organizational image and communication effectiveness. This study employs a qualitative approach using case study methodology, involving participatory observation, in-depth interviews, and document analysis. Data were analyzed using qualitative analysis techniques to identify relevant patterns, themes, and meanings. The theoretical framework underpinning this research is strategic communication and relationship management theory, which emphasizes the significance of PR strategies in building and maintaining positive relationships with the public through the use of digital media. The findings reveal that CRN TV's Public Relations successfully manages content, builds media relations, and utilizes digital platforms for information dissemination. Public engagement and crisis management are also integral components of their communication strategy, proving effective in creating a positive image and strengthening public relationships. The conclusion of this study is that CRN TV's Public Relations plays a crucial role in enhancing organizational image and communication effectiveness through effective PR strategies and the utilization of digital technology.Pentingnya fungsi jurnalistik Humas CRN TV dalam menyajikan informasi akurat dan membangun dialog dua arah antara lembaga dan masyarakat, terutama dalam lingkungan pendidikan, menjadi fokus penelitian ini. Tujuan penelitian ini adalah mengidentifikasi dan mengevaluasi strategi humas dalam memanfaatkan teknologi digital untuk meningkatkan citra organisasi dan efektivitas komunikasi. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, yang melibatkan observasi partisipatif, wawancara mendalam, dan studi dokumentasi. Data dianalisis menggunakan teknik analisis kualitatif untuk mengidentifikasi pola, tema, dan makna yang relevan. Teori yang mendasari penelitian ini adalah teori komunikasi strategis dan manajemen hubungan, yang menekankan pentingnya strategi humas dalam membangun dan memelihara hubungan baik dengan publik melalui pemanfaatan media digital. Hasil penelitian menunjukkan bahwa Humas CRN TV berhasil mengelola konten, membangun hubungan media, dan memanfaatkan platform digital untuk distribusi informasi. Keterlibatan publik dan manajemen krisis juga merupakan bagian integral dari strategi komunikasi mereka, yang terbukti efektif dalam membangun citra positif dan memperkuat hubungan dengan publik. Kesimpulan dari penelitian ini adalah bahwa Humas CRN TV memiliki peran penting dalam meningkatkan citra organisasi dan efektivitas komunikasi melalui strategi humas yang efektif dan pemanfaatan teknologi digital.